Empirical Reassessment of Religious Tolerance in Padang City - Yoan Affandi; Zulfadli Zulfadli; Mhd. Fajri (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2025)
The survey results regarding the level of tolerance in Padang City are low. To increase the Tolerant City Index (IKT), there needs to be an example of the practice of religious tolerance in Padang City to be developed at all levels of local society. This research aims to find practices of religious tolerance in Padang City, with the research locus in Pondok Village. This field research uses a qualitative approach with case study methods. The focus of the study is on the experience and meaning of the practice of religious tolerance in society. Data collection techniques include interviews with a number of parties, such as religious leaders, government officials, administrators of places of worship, and residents. The research results show that the community in Pondok Village represents the practice of religious tolerance through interaction between religious believers, preservation of local culture, and community involvement in various social organizations. Three research findings: 1) Interfaith social interaction in Pondok Village occurs actively and harmoniously; 2) The community in Pondok Village carries out various activities to support the practice of tolerance between religious believers; 3) Citizenship networks are built through community networks and social encounters.